Pendidikan Inklusif untuk ABK: Mewujudkan Kesetaraan dalam Pembelajaran di Sekolah Dasar - Murtiningsih, Lidia (Literasi, 2026)
Inclusive education is an approach that aims to ensure that all children, including children with special needs, have equal opportunities in the learning process. This article examines the importance of implementing inclusive education in primary schools as a step towards realizing equality in education. By identifying the challenges faced by children with disabilities and strategies that educators can implement, the article highlights the role of a supportive school environment, adaptive teaching methods and collaboration between teachers, parents and the community. It also discusses education policies that support inclusion and the importance of teacher training in creating a welcoming classroom for all children. Through inclusive education, children with disabilities can actively participate in the learning process and develop optimally according to their potential.